IT'S A JOB NOT A JAIL : HOW TO BREAK YOUR SHACKLES WHEN YOU CAN'T AFFORD TO QUIT - HOCHHEISER, Roibert M. (Simon & Schuster New YorkUS, 1998)
Promotes the back-scratching technique for surviving in a difficult job situation. Outlines six steps for achieving job satisfaction including: meeting your needs by meeting the needs of others: staying focused; learning from your mistakes; taking charge of your career. Provides practical advice on topics such as: networking, written communication, listening, time management, and, using small talk productively (schmoozing).